Peningkatan Kualitas Pembelajaran Matematika Mahasiswa Berbantuan Python SciPy - Qurohman, M. Taufik; Wardana, Ali; Arif Romadhon, Syaefani (Unity Academy, 2025)
The Community Service Program is a collaboration between Harapan Bersama Polytechnic and Tegal The Community Service Program is a collaboration between Harapan Bersama Polytechnic and Baja Polytechnic Tegal, driven by the need for a more practical and technology-based approach to mathematics education. Students still face challenges in understanding abstract concepts, while the use of scientific computing technologies such as Python and SciPy has not yet been fully integrated into the learning process. This training program is designed to enhance students' understanding through a practical, programming-based approach, covering topics from the basics of Python programming to the application of SciPy in mathematical modeling and problem-solving. The activities are conducted in a participatory manner, encouraging students to actively explore and test concepts directly through digital simulations. Assessment results show significant improvement: students' average scores increased from 50 on the pre-training test to 76 on the post-training test, representing a 52% increase. In addition to quantitative improvements, students also reported tangible benefits in understanding the material and building confidence in using technology in learning. This training demonstrates that the appropriate integration of technology can be an effective solution for enhancing the quality of mathematics education in vocational education settings such as the Baja Polytechnic Tegal.